2008
DOI: 10.1007/s00467-007-0713-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of lupus nephritis in Iranian children: prognostic significance of certain features

Abstract: The objective of this study was to determine the clinical and histopathological features and outcome of children with lupus nephritis (LN). Of 84 children with systemic lupus erythematosus (SLE), we retrospectively studied 58 children (69%) under 15 years of age with biopsy-proven LN who had been followed between October 1989 and January 2005. The mean age at diagnosis or initial referral was 10.6±2.25 years, and the mean followup was 5.3±4.1 years. Class IV LN was observed in 34 (58.6%) patients. The 5-year p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
(37 reference statements)
3
7
2
Order By: Relevance
“…Early diagnosis, better treatment protocols and aggressive management of infections all contribute to the improved outcomes in this severe disease. 10,15,16 Our study confirmed previous reports that elevated creatinine levels prior to the time at diagnosis increased the risk of death. The estimation of prognosis may be enhanced by considering additional features that indicate the reversibility of the renal dysfunction, including the duration of nephritis, the rate of change of serum creatinine, and the renal histology.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Early diagnosis, better treatment protocols and aggressive management of infections all contribute to the improved outcomes in this severe disease. 10,15,16 Our study confirmed previous reports that elevated creatinine levels prior to the time at diagnosis increased the risk of death. The estimation of prognosis may be enhanced by considering additional features that indicate the reversibility of the renal dysfunction, including the duration of nephritis, the rate of change of serum creatinine, and the renal histology.…”
Section: Discussionsupporting
confidence: 82%
“…In our study the mean age and gender distribution was similar to other studies. 7,[10][11][12][13] In contrast to previous reports, we found no statistically significant association in male gender, or onset of disease before puberty (12 years of age) with increased risk of patient survival. This lack of association might be related to recent improvements in accessability to health care in our patient population, differences in our referral patterns from those of other institutions, or to other as yet unrecognized factors.…”
Section: Discussioncontrasting
confidence: 56%
“…LN is characterised by a relapsing and remitting course, requiring close surveillance and prompt treatment to prevent renal damage. Worldwide, the 5-year renal survival rate in children with LN has been shown to vary between 44 and 94 % [10–13]. …”
Section: Introductionmentioning
confidence: 99%
“…It is acknowledged that renal biopsy is not always possible, for instance due to the patient's critical clinical condition or due to lack of resources to safely perform the procedure. Nephrotic syndrome, hypertension and impaired renal function are all correlated with class III/IV LN (26)(27)(28). In cases when a renal biopsy cannot be performed, these symptoms should be considered as reflecting class III/IV LN and treated likewise.…”
Section: Recommendations For Lupus Nephritis -Treatment (Table 2 Figmentioning
confidence: 99%
“…Class III or IV LN, also known as proliferative LN, are the most common and severe forms of LN in cSLE (6,26,27,(39)(40)(41). Combination of class III or IV LN with class V LN is prevalent.…”
Section: Isn/rps Class III and Iv Ln With Or Without Class V Lnmentioning
confidence: 99%